Syndecan-4–/– Mice Have Smaller Muscle Fibers, Increased Akt/mTOR/S6K1 and Notch/HES-1 Pathways, and Alterations in Extracellular Matrix Components - Rønning, Sissel Beate; Carlson, Cathrine Rein; Aronsen, Jan Magnus; Pisconti, Addolorata; Høst, Vibeke; Lunde, Marianne; Liland, Kristian Hovde; Sjaastad, Ivar; Kolset, Svein Olav; Christensen, Geir; Pedersen, Mona Elisabeth (Frontiers in Cell and Developmental Biology, 2020)
Background Extracellular matrix (ECM) remodeling is essential for skeletal muscle development and adaption in response to environmental cues such as exercise and injury. The cell surface proteoglycan syndecan-4 has been reported to be essential for muscle differentiation, but few molecular mechanisms are known. Syndecan-4–/– mice are unable to regenerate damaged muscle, and display deficient satellite cell activation, proliferation, and differentiation. A reduced myofiber basal lamina has also been reported in syndecan-4–/– muscle, indicating possible defects in ECM production. To get a better understanding of the underlying molecular mechanisms, we have here investigated the effects of syndecan-4 genetic ablation on molecules involved in ECM remodeling and muscle growth, both under steady state conditions and in response to exercise. Methods Tibialis anterior (TA) muscles from sedentary and exercised syndecan-4–/– and WT mice were analyzed by immunohistochemistry, real-time PCR and western blotting. Results Compared to WT, we found that syndecan-4–/– mice had reduced body weight, reduced muscle weight, muscle fibers with a smaller cross-sectional area, and reduced expression of myogenic regulatory transcription factors. Sedentary syndecan-4–/– had also increased mRNA levels of syndecan-2, decorin, collagens, fibromodulin, biglycan, and LOX. Some of these latter ECM components were reduced at protein level, suggesting them to be more susceptible to degradation or less efficiently translated when syndecan-4 is absent. At the protein level, TRPC7 was reduced, whereas activation of the Akt/mTOR/S6K1 and Notch/HES-1 pathways were increased. Finally, although exercise induced upregulation of several of these components in WT, a further upregulation of these molecules was not observed in exercised syndecan-4–/– mice. Conclusion Altogether our data suggest an important role of syndecan-4 in muscle development.